2020
DOI: 10.1101/2020.10.23.352294
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 specific memory T lymphocytes from COVID-19 convalescent donors: identification, biobanking and large-scale production for Adoptive Cell Therapy

Abstract: SARS-CoV-2 is causing a second outbreak so the hope for its complete eradication is far from happening. In the absence of effective vaccines, it is mandatory to find effective treatments with low adverse effects able to treat hospitalized patients with COVID-19 disease. In this work, we determined the existence of SARS-CoV-2 specific T cells within the CD45RA- T memory cells from the blood of convalescent donors. Memory T cells can respond quickly to the infection and provide long-term immune protection to red… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…However, Abs alone appear to be insufficient for viral clearance. Adoptive transfer of SARS-CoV-2-enriched T cells from COVID-19 convalescent donors might be a therapeutic option for patients with severe disease ( Ferreras et al., 2020 ; Leung et al., 2020 ), but is restricted by the availability of HLA-matched donors with sufficient SARS-CoV-2-specific T cell frequencies. The risk of graft-versus-host disease (GvHD) due to alloreactivity and the risk of induction of cytokine storm syndrome and lung damage are major concerns ( Mehta et al., 2020 ; Ong et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Abs alone appear to be insufficient for viral clearance. Adoptive transfer of SARS-CoV-2-enriched T cells from COVID-19 convalescent donors might be a therapeutic option for patients with severe disease ( Ferreras et al., 2020 ; Leung et al., 2020 ), but is restricted by the availability of HLA-matched donors with sufficient SARS-CoV-2-specific T cell frequencies. The risk of graft-versus-host disease (GvHD) due to alloreactivity and the risk of induction of cytokine storm syndrome and lung damage are major concerns ( Mehta et al., 2020 ; Ong et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ferreras et al. postulated that in vitro depletion of Tn cells via CD45RA would result in immediately available, ‘off-the-shelf’ SARS-CoV-2-specific memory T cell products ( Ferreras et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a couple of studies have shown that antibody titres decline fast in some convalescent patients, indicating a short duration of humoral immunity (Sette and Crotty, 2021). On the other hand, current studies have demonstrated that specific T cell responses emerge in most of the COVID-19 patients during the early stage of the infection (Ferreras et al, 2021).…”
Section: Introductionmentioning
confidence: 75%
“…However, a couple of studies have shown that antibody titres decline fast in some convalescent patients, indicating a short duration of humoral immunity(Sette and Crotty, 2021). On the other hand, current studies have demonstrated that specific T cell responses emerge in most of the COVID-19 patients during the early stage of the infection(Ferreras et al, 2021). Although significant reduction in T cell counts was observed in severe COVID-19 patients, the revealed antigen specific T cell response indicated their important role in resolving SARS-CoV-2 infection(Grifoni et al, 2020; Le Bert et al, 2020; Weiskopf et al, 2020).…”
Section: Introductionmentioning
confidence: 96%